1998
DOI: 10.1016/s0969-2126(98)00007-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of porcine cathepsin H determined at 2.1 å resolution: location of the mini-chain C-terminal carboxyl group defines cathepsin H aminopeptidase function

Abstract: The crystal structure of cathepsin H reveals that the mini-chain has a definitive role in substrate recognition and that carbohydrate residues attached to the body of the enzyme are involved in positioning the mini-chain in the active-site cleft. Modeling of a substrate into the active-site cleft suggests that the negatively charged carboxyl group of the C terminus of the mini-chain acts as an anchor for the positively charged N-terminal amino group of a substrate. The observed displacements of the residues wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 60 publications
5
117
0
3
Order By: Relevance
“…Cathepsin H enzyme activity was also measured in the presence and absence of 100 µM E-64 with no inhibition observed in either normal or cancer tissues, again demonstrating the specificity of our assay for cathepsin H activity. E-64 is a strong inhibitor of the majority of cysteine proteinases, with the exception of the cysteine proteinase cathepsin H, as reported in biochemical studies (Katunuma and Kominami, 1995) and more recently confirmed by the publication of the crystal structure of porcine cathepsin H (Guncar et al, 1998).…”
Section: Cathepsin H Enzyme Activity: Controls For Assay Specificitymentioning
confidence: 66%
See 2 more Smart Citations
“…Cathepsin H enzyme activity was also measured in the presence and absence of 100 µM E-64 with no inhibition observed in either normal or cancer tissues, again demonstrating the specificity of our assay for cathepsin H activity. E-64 is a strong inhibitor of the majority of cysteine proteinases, with the exception of the cysteine proteinase cathepsin H, as reported in biochemical studies (Katunuma and Kominami, 1995) and more recently confirmed by the publication of the crystal structure of porcine cathepsin H (Guncar et al, 1998).…”
Section: Cathepsin H Enzyme Activity: Controls For Assay Specificitymentioning
confidence: 66%
“…The activity of cathepsin H was determined against the specific synthetic substrate L-Arg-MNA (Sigma; and Enzyme System Products, Dublin, CA, USA) to take advantage of the specific aminopeptidase activity of cathepsin H, that distinguishes it from other cysteine lysosomal enzymes, such as cathepsins B and L (Schwartz and Barrett, 1980;Guncar et al, 1998). Tissue extracts (10-20 µl per assay) were pre-incubated in assay buffer (0.1 M MES-EDTA buffer, 1 mM dithiothreitol (DTT), pH 6.8) at 37°C for 5 min, using a modification of methods described by Schwartz and Barrett (1980).…”
Section: Cathepsin H Enzyme Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…To address the convergence and robustness of refinement, we chose five starting cases of molecular-replacement solutions of the crystal structures of cathepsin H (PDB entry 8pch; Gunčar et al, 1998) Kim et al, 2006). The structures of actinidin (Baker, 1980), Crotalus atrox phospholipase A 2 (Keith et al, 1981), stefin B (Stubbs et al, 1990), thaumatin (Ko et al, 1994) and choline acetyltransferase (Cai et al, 2004) were used as the search models (Pražnikar et al, 2009).…”
Section: Molecular-replacement Test Cases and Electron-density Map Camentioning
confidence: 99%
“…These features compete with inhibitors for binding into the same sites on the surface of target proteases. According to the model of cystatin-papain-like protease complex N-terminal trunk competes with the features of aminopeptidases: the mini-chain of cathepsin H [20] and the exclusion domain residues of cathepsin C [21], whereas the second hairpin loop competes for binding with the occluding loop of carboxypeptidase cathepsin B [22].…”
Section: Inhibitory Properties Of Mouse Stfa1 and Stfa2mentioning
confidence: 99%